L-NAME causes antinociception by stimulation of the arginine-NO-cGMP pathway - I. D. G. Duarte; S. H. Ferreira (Hindawi Limited, 2000)
NG-nitro-L-arginine methyl ester (L-NAME) has been used extensively as a paradigmatic inhibitor of NO synthase and has been shown to cause antinociception in several experimental models. We describe here how L-NAME produced a dose-dependent anti-nociceptive effect when injected intraperitoneally in the mouse after acetic acid induced writhings, or intraplantarly in the rat paw pressure hyperalgesia induced by carrageenin or prostaglandin E2. In contrast another NO synthase inhibitor, NG-monomethyl-L-arginine (L-NMMA), had no significant effect per se but inhibited L-NAME systemic induced antinociception in mice and local induced antinociception in the rat paw hyperalgesia test. D-NAME had no anti-nociceptive effect upon carrageenin-induced hyperalgesia. Pretreatment of the paws with two inhibitors of guanylate cyclase, methylene blue (MB) and 1H-:[1,2,4]-oxadiazolo-:[4,3-a] quinoxalin-1-one (ODQ) abolished the antinociceptive effect of L-NAME. L-Arginine and the cGMP phosphodiesterase inhibitor, MY 5445 significantly enhanced the L-NAME antinociceptive effect. The central antinociceptive effect of L-NAME was blocked by co-administration of L-NMMA, ODQ and MB. The present series of experiments shows that L-NAME, but not L-NMMA, has an antinociceptive effect. It can be suggested that L-NAME causes the antinociceptive effect by stimulation of the arginine/NO/cGMP pathway, since the antinociceptive effect of L-NAME can be antagonized by L-NMMA and abolished by the guanylate cyclase inhibitors (MB and ODQ). In addition, the NO synthase substrate, L-arginine and the cGMP phosphodiesterase inhibitor, MY5445 were seen to potentiate the effects of L-NAME. Thus, L-NAME used alone, has limitations as a specific inhibitor of the arginine-NOcGMP pathway and may therefore be a poor pharmacological tool for use in characterising participation in pathophysiological processes.